2008
DOI: 10.1371/journal.pone.0003854
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Gastrokine-1 Purified from Chicken Gizzard Smooth Muscle

Abstract: The potential role and function of gastrokine-1 (GNK1) in smooth muscle cells is investigated in this work by first establishing a preparative protocol to obtain this native protein from freshly dissected chicken gizzard. Some unexpected biochemical properties of gastrokine-1 were deduced by producing specific polyclonal antibody against the purified protein. We focused on the F-actin interaction with gastrokine-1 and the potential role and function in smooth muscle contractile properties.BackgroundGNK1 is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Secretion of gastrokine-2 by YS endodermal cells is yet to be formally demonstrated. Gastrokine-1 protein associates with F-actin (Hnia et al, 2008). In contrast, Gkn2 protein was most found in the basal side of the YS endoderm, whereas F-actin in the YS is concentrated at the inner leaf of the apical cell membrane facing the maternal tissue suggesting that the majority of YS gastrokine-2 is not associated with F-actin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Secretion of gastrokine-2 by YS endodermal cells is yet to be formally demonstrated. Gastrokine-1 protein associates with F-actin (Hnia et al, 2008). In contrast, Gkn2 protein was most found in the basal side of the YS endoderm, whereas F-actin in the YS is concentrated at the inner leaf of the apical cell membrane facing the maternal tissue suggesting that the majority of YS gastrokine-2 is not associated with F-actin.…”
Section: Discussionmentioning
confidence: 93%
“…Gastrokine-1 protein has been shown to associate with filamentous (F)-actin (Hnia et al, 2008). We therefore assessed the localisation of gastrokine-2 protein in the YS compared to F-actin as indicated by phalloidin binding ( Fig.…”
Section: Gastrokine-2 Protein Expression In the Ysmentioning
confidence: 99%
“…Because chicken GKN1 has been proved to interact with cytoskeleton by exerting a cytoprotection action [21], we investigated the potential association of human GKN1 with actin in both gastric cancer cells and in solution. Compared to cancer gastric tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggested that the N-terminal GKN1 sequence is important for its interaction with cellular compartments involved in the secretory mechanism. Hnia et al [21] showed that chicken GKN1 was well distributed throughout the gastric epithelium, but also colocalized and directly interacted with actin in smooth muscle cells probably through the presence of two or possibly three predicted trans-membrane helices. Also mature human GKN1, as predicted at TMpre Swiss Institute of Bioinformatics [25], was predicted as type II TM protein (N-terminus inside and 2 strong transmembrane helices F3-A20 and L158-V174), which might explain its prevalent membrane localization (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation